(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper,we have been obtainedMLE and Bayes Estimator of utilization factor in Power Supplyqueuing model based on requirement of power forthe number of customers at various sampled time points. We have been checked the consistency of maximum likelihood estimator of utilization factor and find the confidence interval for expected MLE of it.Bayes estimators of utilization factor havealso been obtained.We also derive the expression for Expectation of MLE of ρ, Bayes estimate of ρ under squared error loss function. Fordifferent choices of hyper-parametersthe minimum posterior risk of this Bayes estimator has also been obtained numerically by using R software packages.